Una nueva hipótesis sobre las primeras etapas de la evolución tectosedimentaria de la cuenca pérmico-triásica del SE de la Cordillera Ibérica. - Arche, A.; López-gómez, José (Cuadernos de Geología Ibérica, 1992)
Ihe Buntsandstein facies represents the first stages of the tecto-sedimentary evolution of the SE Iberian Ranges and consists of four continental formations, basically fluvial, associated in two fining-upwards macrosequences. `Itere is an important angular unconformity, at the base and two hiatuses, nne in the middle part and another at the top. `Ile SE [berian ]3asin appears at ffie end of the Permian as an endorreic depression with a semigraben structure, limited by NW-SE normal faults and evolves towards a classic graben during the Early Triassic. The boundary faults are interpreted as listric faults dying out at perhaps 12-15 Kms, instead deep-seated, alniost vertical faults as in pre’vious reconstructions. A NNE-SSW fault system represents a transfert system of the main NW-SE faults, increasing their throw towards the SE and from the upper Permian. The orientation and morphology of the general faulí systems will control the movement of later thrust faults dwing the Tertiary.